Association of visit-to-visit variability of systolic blood pressure with cardiovascular disease, chronic kidney disease and mortality in patients with hypertension. Issue 5 (May 2020) - Wan, Eric Yuk Fai; Yu, Esther Yee Tak; Chin, Weng Yee; Fong, Daniel Yee Tak; Choi, Edmond Pui Hang; Lam, Cindy Lo Kuen
Abstract : Objective: This study aimed to evaluate the association between visit-to-visit variability of systolic blood pressure (SBP) and cardiovascular disease, chronic kidney disease, and mortality among hypertensive patients. Methods: A population-based cohort included 225 759 Chinese hypertensive adults without diabetes, cardiovascular disease, and chronic kidney disease during 2011–2012. SBP variability was determined based on standard deviations of SBP over the previous 5 years before baseline. Cox regressions adjusted with patients' baseline characteristics, mean, and temporal trend of SBP was applied to the associations between variability and incident cardiovascular disease, chronic kidney disease and all-cause mortality. Results: In all, 25 714 patients with cardiovascular disease, 27 603 with chronic kidney disease, and 16 778 deaths have occurred during the median follow-up of 70.5 months (1.2 million person-years). SBP variability was continuously and positively associated with higher cardiovascular disease, chronic kidney disease and mortality risk among hypertensive patients without evidence of a threshold. Each 10-mmHg increase in SD of SBP was associated with 35% [hazard ratio 1.35, 95% confidence interval (CI) 1.30–1.39], 39% (HR 1.39, 95% CI 1.35–1.43), and 40% (HR 1.40, 95% CI 1.34–1.45) higher risk of cardiovascular disease, chronic kidney disease and mortality, respectively. HRs were attenuated with increased age, mean SBP, and Charlson index, and decreased temporal trend of systolic blood pressure, but it remained significant and consistent in most of the different subgroups. Conclusions: Findings suggested that SBP variability is a significant prognostic value, in addition to baseline or mean of SBP for the risk of cardiovascular disease and mortality. Abstract : Supplemental Digital Content is available in the text